Analisis Kadar Nitrogen, Fosfor dan Kalium Pada Lahan Tambang Aspal Buton - Peliyarni Peliyarni; Muh. Noor Azizu; Wulan Riski Yanti; Ridwan Ridwan (BioWallacea : Jurnal Penelitian Biologi (Journal of Biological Research), 2022)
Asphalt resources in Buton Island, Southeast Sulawesi Province are the only natural asphalt deposits in Indonesia. In addition to Indonesia, natural asphalt deposits are found in the Trinidad Islands, Albania and Iraq which are used for road coatings, building roofs, mastic flooring, paving mixes and paint mixtures. This study analyzes the levels of Nitrogen, Phosphorus and Kaliam at three asphalt mining locations, namely: heaps from asphalt processing, unprocessed asphalt land and locations from mining processing. The sample was taken from Nambo Village, Lasalimu District, Buton Regency, where the entire area is an asphalt mine. This study aims to provide solutions to the community regarding the handling of nutrient levels in asphalt mining land so that it can be used as agricultural land. The research was conducted through several stages including: Preparation of Tools and Materials; Sample Preparation; Analysis of Soil Nutrient Levels (includes: elemental N analysis, elemental analysis of P and analysis of elemental K). The results obtained that the highest soil nitrogen content was found in asphalt mining waste, namely 0.39% at a depth of 25 cm and 0.27% at a depth of 50 cm, while the lowest nitrogen content was found in soil without mining activities, namely 0.1 at a depth of 50 cm. at a depth of 25 cm and 0.07 at a depth of 50 cm. The highest phosphorus levels were found in soil without mining activities, namely 1302 mg/100g at a depth of 25 cm and 1518 mg/100g at a depth of 50 cm, while the lowest phosphorus levels were found in ex-mining soil, namely 329 mg/100g at a depth of 25 cm and 405 g. mg/100g at a depth of 50 cm. The highest potassium levels were found in soil without mining activities, namely 569 mg/100g at a depth of 25 cm and 521 mg/100g at a depth of 50 cm, while the lowest potassium levels were found in ex-mining soil, which was 127 mg/100g at a depth of 25 cm. and 128 mg/100g at a depth of 50 cm.